BVGer D-4996/2019 vom 2. September 2019 - Bundesverwaltungsgericht (2019)
Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung) | Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung); Verfügung des SEM vom 2. September 2019